Bleuler's Psychopathological Perspective on Schizophrenia Delusions: Towards New Tools in Psychotherapy Treatment - Arantes-Gonçalves, Filipe; Gama Marques, João; Telles-Correia, Diogo (Frontiers in Psychiatry, 2018)
The authors begin by addressing the historical evolution of the delusion concept and its different approaches, focusing afterwards mainly on the work of Bleuler, who stressed the proximity between delusions and the emotional life of patients with schizophrenia. In this article it is aimed to review the main aspects of the theory of delusion formation in schizophrenia according to Bleuler´s psychopathological perspective. For that purpose first the role of delusions in the psychopathology of schizophrenia is explored in a close relation with the Bleuler´s fundamental symptoms (Alogia, Autism, Ambivalence and Affect Blunting) nowadays known as negative symptoms. Then, persecutory, grandiosity and sexual delusions in schizophrenia are described according to the tension between logic and affects, as well as, internal conflict, schizoid features and auto-erotism as key psychopathological pathways. Thus, with this subjective perspective, it is intended to highlight Bleuler´s psychopathological contribution to the affective and meaningful causality of delusions in schizophrenia. The former might be useful in the integration with other psychopathological phenomena (hallucinations and negative symptoms) and new forms of research and therapeutic approaches in this disorder that are complementary with the contemporary tendencies in psychopathology.